תן f (x) = x ^ 2 ו- g (x) = x-3. מהו הערך של (g * f) (3.5)?

תן f (x) = x ^ 2 ו- g (x) = x-3. מהו הערך של (g * f) (3.5)?
Anonim

תשובה:

ראה את כל תהליך הפתרון הבא:

הסבר:

# (g * f) (x) = g (x) * f (x) = (x - 3) x ^ 2 #

לכן:

# (g * f) (x) = (x - 3) x ^ 2 #

למצוא # (g * f) (3.5) # אנחנו חייבים להחליף #color (אדום) (3.5) # עבור כל התרחשות של #color (אדום) (x) # in # (g * f) (x) #

# (x * f) (צבע (אדום) (x)) = (צבע (אדום) (x) - 3) צבע (אדום) (x) ^ 2 # הופ post

# (g * f) (צבע (אדום)) 3.5 () = (צבע (אדום) (3.5) - 3) (צבע (אדום)) 3.5 () ^ 2 #

# (g * f) (צבע אדום) (3.5)) = 0.5 (xx) צבע (אדום) (3.5)) ^ 2 #

# (g * f) (צבע) (אדום) (3.5)) = 0.5 xx (צבע (אדום) (3.5)) ^ 2 #

# (g * f) (צבע (אדום) (3.5)) = 0.5 xx 12.25 #

# (g * f) (צבע (אדום) (3.5)) = 6.125 #